Changes in root porosity and water soluble carbohydrates in rice (Oryza sativa L.) under submergence stress: Responses of rice as under submergence stress (Journal of the Bangladesh Agricultural University, 2019)
Submergence stress at early vegetative stage is one of the most important constraints in the productivity of rice in Bangladesh. Submergence causes yield loss of rice at Aman season in Bangladesh and therefore, it is necessary to develop submergence tolerant rice cultivars. A pot experiment was conducted at the net house of Department of Crop Botany, Bangladesh Agricultural University, during Aman season from July to December, 2017 to evaluate the changes in root porosity and water soluble carbohydrates (WSCs) associated with submergence tolerance in rice. The experiment consisted of two factors—(i) Rice cultivars (Binadhan-11, Binadhan-12, BRRI dhan51 and BRRI dhan52 as tolerant and BRRI dhan49 as susceptible) and(ii) Submergence stress: Submergence for 14 days at vegetative stage and control. Submergence stress was imposed by dipping of pots into a water tank with about 90 cm depth of water while the control plants are maintained in the pot house of the field laboratory. The plants were sampled at seven days interval during submergence to determine the changes in root porosity and to examine the contribution of shoot reserves for their survival. The root porosity was measured by pycnometer method and water soluble carbohydrate was measured by the anthrone method. Tolerant cultivars showed greater root porosity development in both control and stress condition but the susceptible cultivar showed significantly lower root development in stress condition. Higher root porosity might help tolerant cultivars to survive in submergence stress more efficiently. Tolerant rice cultivars had high initial soluble carbohydrate than the susceptible one. Under submergedcondition, the tolerant cultivars showed slow depletion of water soluble carbohydrate compared to susceptible cultivar. Higher carbohydrate contents in tolerant cultivars might act as buffer stock during submergence for their better survival and growth.J Bangladesh Agril Univ 17(4): 539–544, 2019